Neuroticism and internet addiction: What is next? A systematic conceptual review. (February 2022) - Marciano, Laura; Camerini, Anne-Linda; Schulz, Peter J.
Abstract: The personality trait of neuroticism (N) has consistently shown to be a risk factor for Internet Addiction (IA). Review literature, however, looked at this in bivariate analyses only. To the best of our knowledge, we conducted the first review that systematically and conceptually summarized results based on the inclusion of additional factors, thus coming closer to the complex nature of the relationship of N with IA. Through a systematic search, we identified 56 studies investigating the relationship between N, IA, and other variables. We grouped the latter in: (i) internalizing problems, (ii) externalizing problems, (iii) coping style, (iv) well-being, and (v) other factors. Based on our findings, we propose a theoretical model, which would move a step forward towards the understanding of long-term consequences of IA. Hence, in the proposed model, N (predictor) would predict IA, which, in turn, would predict health-related consequences (outcome) – including internalizing and externalizing symptoms, general well-being, and low academic/cognitive performance. Coping style, maladaptive cognitions, and low cognitive control would partially mediate the link between N and IA, whereas gender, age, and social context would moderate the hypothesized relationships. The proposed theoretical model should pave the way to longitudinal research on the role of IA in neurotic (N) people to eventually inform public health policies. Highlights: Neuroticism is a consistent risk factor for internet addiction. The present systematic conceptual review includes 56 studies on this link. Other factors are internalizing and externalizing problems, coping, and well-being. The proposed theoretical model includes internet addiction as a mediator.